Is spinal tuberculosis changing with changing time?. (June 2021) - Hasan Khan, Mohammad Noah; Jamal, Abdul Basit; Hafeez, Auzair; Sadiq, Marium; Rasool, Muhammad Umer
Abstract: Introduction: Spinal tuberculosis is a chronic destructive disease with long-term morbidity. Patients are usually young especially from a poor socioeconomic background. Destruction of the intervertebral disk space and the adjacent vertebral bodies is the characteristic lesion. The dorsal spine is the most affected region with multi-level noncontiguous involvement being detected more frequently. Patients usually present with chronic back pain associated with spinal tenderness, paraplegia, spinal deformities, as well as with constitutional symptoms. Magnetic resonance imaging has proved to be more sensitive and specific for its diagnosis, but availability and affordability of this investigation remain a problem in developing countries. Anti-tuberculous drug therapy has revolutionized the treatment of this debilitating disease. Surgery is still required in selected cases especially with evolving neurological deficit, progressive deformity, intractable pain and lack of response to drug therapy. With early diagnosis and effective treatment, prognosis is generally good. Materials/Methods: After getting permission from the clinical governance department, We collected the retrospective data of 305 patients with diagnosed spinal tuberculosis, who underwent surgical intervention. Results: There was no significant difference in incidence among males and females. Housewives were the most affected. Lower dorsal spinal was the commonest site involved but our study didn't confirm the incidence of multi-level disease process. Anterior decompression along with Cage fixation was most frequently performed procedure. Conclusion: Despite the availability of highly effective antituberculous drugs, advanced surgical procedure, the spinal tuberculosis still maintains its demographic profile. There has been no change in characteristics of spinal presentation of this chronic debilitating disease. Patients continue to suffer the same way as they were suffering decades ago. Highlights: Spinal tuberculosis is a chronic destructive disease with long-term morbidity. The dorsal spine is the most affected region with multi-level involvement being detected. Analysis of data of 305 patients with diagnosed spinal tuberculosis, who underwent surgical intervention. Despite the availability of highly effective drugs, and surgical procedure, the spinal tuberculosis still maintains its demographic profile. There has been no change in characteristics of spinal presentation of this chronic debilitating disease.